The Impact of Antioxidants from the Diet on Breast Cancer Cells Monitored by Raman Microspectroscopy - Medeiros, Paula S. C.; de Carvalho, Ana Lúcia Marques Batista; Ruano, Cristina; Otero, Juan C.; Marques, Maria Paula Matos (Letters in Drug Design & Discovery, 2019)
Background: The impact of the ubiquitous dietary phenolic compound p-coumaric acid on human breast cancer cells was assessed, through a multidisciplinary approach: Combined biological assays for cytotoxicity evaluation and biochemical profiling by Raman microspectroscopic analysis in cells. Methods: Para-coumaric acid was shown to exert in vitro chemoprotective and antitumor activities, depending on the concentration and cell line probed: a significant anti-invasive ability was detected for the triple-negative MDA-MB-231 cells, while a high pro-oxidant effect was found for the estrogen- dependent MCF-7 cells. A striking cell selectivity was obtained, with a more noticeable outcome on the triple-negative MDA-MB-231 cell line. Results: The main impact on the cellular biochemical profile was verified to be on proteins and lipids, thus justifying the compound´s anti-invasive effect and chemoprotective ability. Conclusion: p-Coumaric acid was thus shown to be a promising chemoprotective/chemotherapeutic agent, particularly against the low prognosis triple-negative human breast adenocarcinoma.
Keywords: chemoprotective/chemotherapeutic